Farming, Reported Pesticide Use, and Prostate Cancer. (March 2013) - Ragin, Camille; Davis-Reyes, Brionna; Tadesse, Helina; Daniels, Dennis; Bunker, Clareann H.; Jackson, Maria; Ferguson, Trevor S.; Patrick, Alan L.; Tulloch-Reid, Marshall K.; Taioli, Emanuela
Prostate cancer is the leading cancer type diagnosed in American men and is the second leading cancer diagnosed in men worldwide. Although studies have been conducted to investigate the association between prostate cancer and exposure to pesticides and/or farming, the results have been inconsistent. We performed a meta-analysis to summarize the association of farming and prostate cancer. The PubMed database was searched to identify all published case–control studies that evaluated farming as an occupational exposure by questionnaire or interview and prostate cancer. Ten published and two unpublished studies were included in this analysis, yielding 3, 978 cases and 7, 393 controls. Prostate cancer cases were almost four times more likely to be farmers compared with controls with benign prostate hyperplasia (BPH; meta odds ratio [OR], crude = 3.83, 95% confidence interval [CI] = 1.96-7.48, Q -test p value = .352; two studies); similar results were obtained when non-BPH controls were considered, but with moderate heterogeneity between studies (meta OR crude = 1.38, 95% CI = 1.16-1.64, Q -test p value = .216, I 2 = 31% [95% CI = 0-73]; five studies). Reported pesticide exposure was inversely associated with prostate cancer (meta OR crude = 0.68, 95% CI = 0.49-0.96, Q -test p value = .331; four studies), whereas no association with exposure to fertilizers was observed. Our findings confirm that farming is a risk factor for prostate cancer, but this increased risk may not be due to exposure to pesticides.